PENGARUH INDEPENDENSI, SKEPTISISME DAN GENDER PADA PERTIMBANGAN MATERIALITAS DAN IMPLIKASINYA PADA KETEPATAN PEMBERIAN OPINI AUDITOR - Winadi, Ni Gusti Ayu Ratih Ary; Mertha, I Made (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
Appropriateness of granting the auditor's opinion can be assessed based on the factors affecting the level of materiality considerations. The purpose of this study is to provide empirical evidence of the influence of the independence, professional skepticism auditors, and gender in the precision of the provision of the auditor's opinion and with consideration of materiality levels at the public accounting firm in the city of Denpasar. The sampling method used is the method of saturated samples. Questionnaires were distributed numbered 65 and 40 questionnaires were filled in completely and can be processed. Analysis for hypothesis testing was done with path analysis. Results of regression analysis found that the auditor's independence and professional skepticism has a positive influence on the precision of the provision of the auditor's opinion. Auditor independence and professional skepticism also has a positive effect on the accuracy of the auditor's opinion giving consideration materiality levels.
Keywords: independence, skepticism, gender, materiality, opinions